2017
DOI: 10.1017/psrm.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Economic Perceptions and Electoral Choices: A Design-Based Approach

Abstract: Do economic perceptions affect voters’ electoral choices? There is ample evidence showing a correlation between how people perceive the current state of the economy and electoral decisions. However, there are reasons to believe that political preferences can also determine how voters evaluate economic conditions, which will reverse the causality arrow. The strategies previously implemented to address this problem have been based on the use of structural equations and instrumental variables, but they require ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
(102 reference statements)
1
11
0
Order By: Relevance
“…These articles contribute to a growing literature on the dynamics of approval in presidential systems (e.g., Arce and Carrión, 2010;Carlin, Carreras and Love, forthcoming;Cuzán and Bundrick, 1997;Carlin, Hartlyn and Martínez-Gallardo, 2012;Johnson and Schwindt-Bayer 2009;Pérez-Liñán, 2007) by highlighting a set of factors that explain why some presidents deviate from the typical cyclical pattern. In line with previous research on economic voting in Latin America (e.g., Boelhouwer Menezes, 2018;Benton, 2005;Cabezas, 2015;Cabezas and Navia, 2010;Echegaray, 2005;Gélineau, 2007;Johnson and Schwindt-Bayer, 2009;Lewis-Beck and Ratto, 2013;Love and Windsor, 2018;Luna, 2002;Menezes, 2018;Murillo and Visconti, 2017;Singer, 2013Singer, , 2015Singer and Carlin, 2013;Visconti, 2017), all of the authors in this special issue agree that economic outputs -and economic perceptions of performance-go a long way in explaining patterns of executive approval. Also in line with previous work (Powell and Whitten, 1993), some of the articles find that institutions can alter patterns of approval.…”
Section: Case Studies Of Outliers Of Presidential Approvalsupporting
confidence: 85%
“…These articles contribute to a growing literature on the dynamics of approval in presidential systems (e.g., Arce and Carrión, 2010;Carlin, Carreras and Love, forthcoming;Cuzán and Bundrick, 1997;Carlin, Hartlyn and Martínez-Gallardo, 2012;Johnson and Schwindt-Bayer 2009;Pérez-Liñán, 2007) by highlighting a set of factors that explain why some presidents deviate from the typical cyclical pattern. In line with previous research on economic voting in Latin America (e.g., Boelhouwer Menezes, 2018;Benton, 2005;Cabezas, 2015;Cabezas and Navia, 2010;Echegaray, 2005;Gélineau, 2007;Johnson and Schwindt-Bayer, 2009;Lewis-Beck and Ratto, 2013;Love and Windsor, 2018;Luna, 2002;Menezes, 2018;Murillo and Visconti, 2017;Singer, 2013Singer, , 2015Singer and Carlin, 2013;Visconti, 2017), all of the authors in this special issue agree that economic outputs -and economic perceptions of performance-go a long way in explaining patterns of executive approval. Also in line with previous work (Powell and Whitten, 1993), some of the articles find that institutions can alter patterns of approval.…”
Section: Case Studies Of Outliers Of Presidential Approvalsupporting
confidence: 85%
“…Of course, the nature of a conjoint experiment, in which respondents evaluate hypothetical candidates, raises the question of whether respondents would make the same decisions in real life. Nevertheless, different studies have validated results from conjoint analyses by comparing them with behavioral benchmarks in Switzerland (Hainmueller et al 2015) and Chile (Visconti 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Even though ideology may seem to have been relegated to a lesser role in citizens' electoral decisions, recent findings show that ideological labels may still be important to Chilean voters. For example Visconti (2018) provides evidence from the combination of a natural and a survey experiment to show how voters from a low-to-middle-income locality in northern Chile use ideological labels to identify the candidate most likely to pass the policies they need after a natural disaster.…”
Section: The End Of Ideology In Chile?mentioning
confidence: 99%
“…National economic perceptions are a relevant issue in Latin American political behavior, as several works suggest the existence of sociotropic economic voting (Lewis-Beck and Ratto, 2013;Singer and Carlin, 2013). However, Latin America remains mostly unexplored regarding the influence of partisanship on economic perceptions except for Visconti (2017) and Samuels and Zucco's (2018) work. Visconti's (2017) article provides evidence from observational data of partisan bias in economic perceptions in two minor Brazilian cities.…”
Section: The Uruguayan Casementioning
confidence: 99%
“…Regardless of whether Uruguay's economic performance is a factor of merit or chance, its overall economic position is important because in less stable economies, partisan contamination of voters' economic evaluations have proved to be much less likely (Evans and Andersen, 2006). As Visconti (2017;p. 3) posits: «Citizens from lower socioeconomic contexts should be more sensitive to changes in their income than citizens from developed countries because these events are likely to have a more meaningful effect on their living conditions». Furthermore, the main antecedent study on the relation between economic perceptions and partisanship in Uruguay concluded that partisanship does not affect Uruguayans economic views (Luna, 2002) while evidence of economic vote in Uruguay has been illustrated in a few studies (Queirolo, 2013;Carlin et al, 2015).…”
Section: The Uruguayan Casementioning
confidence: 99%